Why women or why not men? sex and autoimmune diseases - Gilberto Cincinelli; Elena Generali; Rajkiran Dudam; Vinod Ravindran; Carlo Selmi (Indian Journal of Rheumatology)
The epidemiology of autoimmune diseases is characterized by a significant sex dimorphism, with the majority of disorders being more prevalent in women. In a parallel fashion, the immune system shows sex-dependent differences in number and functions of both its innate and its adaptive arms, with women capable to mount a more vigorous response compared to men. This enhanced reactivity may contribute to the stronger defense against infectious agents and to the reasons for which, on the other hand, women are more prone to develop autoimmune diseases. Several factors have been studied and implied to play a role for such an imbalance, most notably sex chromosomes, sex hormones, and gut microbiota differences between sexes. Experimental studies on rodents demonstrate that sex chromosome abnormalities, alterations of gut microbiota composition, and fluctuations of sex hormone concentrations decrease the susceptibility to autoimmunity in female probes or increase it in the male counterparts. Nevertheless, it would be reductive to consider sex only as a risk factor; based on clinical experience, autoimmune disease onset and course differ between men and women in terms of disease progression and severity. Eventually, research has focused on sex as a determinant of antirheumatic treatment response with promising evidence for a further personalized management of patients with autoimmune diseases.